RZYMSKA SOCIETAS A PARTNERSHIP SYSTEMU COMMON LAW - Dziuban, Ewa (Zeszyty Prawnicze, 2017)
ROMAN SOCIETAS AND THE COMMON LAW PARTNERSHIP The construction of roman societas in comparison with the common law partnership was the subject of authors inquiry. The idea was to find whether these two contracts, being created in a very different time and situation, with ages of various experiences between them, could, in some way, resemble. In other words - is that possible that the similar aim of the contracts determined the shape of the legal form? Both constructions were analysed stressing their most significant points. The comparison was led due to the pattern established by the author, created to make it more readable. As a result every characteristic was composed of the following parts: 1. description of the contract’s nature; 2. types of the contract; 3. inner relations between partners; 4. societas/partnership in relation to outer world; 5. dissolving the contract. On this basis author examined the findings. The pointed conclusions seemed to provide a very interesting start for further inquiries. The reason for this is, as it occurred, that between two legal systems, existing in separate ages and conditions, with settled opinion on their incompatibility, more than few similarities can be found. Author did not give a straight answer to the question why these similarities really exist. In fact she provides at least two possible explanations without prejudice. Actually to give a more exact answer deeper studies shall be undertaken. However even at this very early stage it can be said, that both constructions, even though so faraway in various dimensions from each other, developed compatible solutions on their way to find the best idea how the goal can be achieved. And this goal, as it occurred from the contracts’ nature, seemed to be analogous. Is the similar solution a question of reception? Or maybe both systems parallel found the way, which occurred to be the best and, in the same time, convergent? Maybe the catalogue of best solutions is closed and sooner or later every system shall come to it? These questions must be asked. Even if or especially that the answers are neither easy nor immediate. Author finished this first stage of her studies leaving them open but with the reservation that inquiry will be continued.